Changes in basal and insulin and amino acid response of whole body and skeletal muscle proteins in obese men - Guillet, Christelle; Delcourt, Ingrid; Rance, Melanie; Giraudet, Christophe; Walrand, Stephane; Bedu, Mario; Duche, Pascale; Boirie, Yves (The journal of clinical endocrinology and metabolism, 2009)
Obesity-related insulin resistance of glucose and lipid metabolism may also affect protein kinetics, notably at the muscle level. We hypothesized that muscle protein response to insulin and amino acid is blunted during obesity. Total (Tot) and mitochondrial (Mit) muscle proteins fractional synthesis rates (FSR) together with whole-body protein kinetics (WB) have been determined in postabsorptive state (PA) and during a hyperinsulinemic, hyperaminoacidemic, euglycemic clamp by using a continuous infusion of (13)C-leucine in six obese and eight nonobese subjects. Responses of WB glucose disposal rate and protein breakdown to insulin and amino acid infusion were significantly lower in obese than in nonobese subjects (P < 0.05). In PA, Tot and Mit FSR were significantly lower (P < 0.05) in obese (Tot, 0.044 +/- 0.005% . h(-1); Mit, 0.064 +/- 0.008% . h(-1)) in comparison with nonobese subjects (Tot, 0.082 +/- 0.010% . h(-1); Mit, 0.140 +/- 0.006% . h(-1)). Tot FSR was similarly stimulated by insulin and amino acid in both groups (0.094 +/- 0.013 vs. 0.117 +/- 0.006% . h(-1), obese vs. nonobese; P < 0.05). Mit FSR was increased in nonobese subjects (0.179 +/- 0.007% . h(-1); P < 0.05) but not in obese subjects (0.078 +/- 0.012% . h(-1); P = not significant). The obesity-related impairment of protein metabolism is characterized by 1) a reduced turnover rate of skeletal muscle proteins in PA; 2) a lack of stimulation of mitochondrial protein synthesis by insulin and amino acid; and 3) a lower inhibition of WB proteolysis by insulin and amino acid. Alterations of selective muscle protein kinetics may predispose obese subjects to muscle metabolic dysfunction leading to type 2 diabetes.